Annotated record of the detailed examination of Mn deposits from DSDP Site 76, Leg 9 (Cores 76-1, 76A-1) - J D Hays; Harry E III Cook; D Graham Jenkins; F M Cook; J T Fuller; Robert M Goll; E Dean Milow; W N Orr (PANGAEA, 1972)
Site 76 was selected in order to core a thick sequence of sediments north of the Tuamotu ridge that had been crossed by Glomar Challenger justprior to the termination of Leg 8 in Tahiti. Two holes at this site continuously cored 27 meters of lower Pliocene to Recent phillipsitic clay and calcareous nannofossil ooze interbedded with calcareous turbidites. The drill bit was stopped by a silicified calcareous turbidite of Early Pliocene age.
Supplement to: Hays, JD et al. (1972): Site 76. In: Hays, J.D.; et al., Initial Reports of the Deep Sea Drilling Project, Initial Reports of the Deep Sea Drilling Project, 9, U.S. Government Printing Office, IX, 21-41, https://doi.org/10.2973/dsdp.proc.9.102.1972